THE Y- INDEX AND COINDEX OF V C5C7[p, q] AND HC5C7[p, q] NANOTUBES - Alsharafi, M.; Alameri, A.; Zeren, Y. (TURKIC WORLD MATHEMATICAL SOC, 2024)
The Y-index and coindex are degree based molecular structure descriptors that have been shown to give a high degree of predictability compare to Zagreb indices and F-index and their coindices for some physicochemical properties of octane isomers. In this paper, we studied the Y - index and Y - coindex for certain important chemical structures like line graphs of the V C5C7[p, q] and HC5C7[p, q] nanotubes and their molecular complement graph. Moreover, we defined Y - polynomial of graph G and applied it on the line graphs of the V C5C7[p, q] and HC5C7[p, q] nanotubes. These explicit formulae can correlate the chemical structure of molecular graph of nanotube to information about their physical structure.
Keywords: Y -index; Y-coindex; VC5C7 [ p, q ] nanotube; HC 5 C 7 [ p; molecular; graph; molecular complement graph.; Mathematics